Factors Affecting Compliance with Infection Control Measures among Nurses during the COVID-19 Pandemic: A Qualitative Study - Nojoud Alrashidi (Hail Journal of Health Sciences)
Introduction: Nurses must have the knowledge and abilities to protect themselves and others from the potential injuries confronted. This study aimed to understand what contributes to the experience of not adhering to the infection control measures. Methods: This study was designed using the qualitative–thematic analysis method with ten staff nurses at the COVID centers of the Hail region, Kingdom of Saudi Arabia. The data were gathered from November 2021 to the 1st week of January 2022. Results: Four themes emerged from the interview data: inadequate resources, a shortage of health-care personnel, ward organization, and self-sacrifice. The inadequate materials, a shortage of health-care personnel, and the organization of the ward may have interfered with their capability to conduct the COVID-19 preventive actions, but self-sacrificing has emerged despite such experience. Conclusions: Therefore, the need for adequate resources, expert staffing, and further motivation (of any kind) can ensure quality health-care services during this public health emergency.